Long reads and Hi‐C sequencing illuminate the two‐compartment genome of the model arbuscular mycorrhizal symbiont Rhizophagus irregularis. Issue 3 (24th November 2021) - Yildirir, Gökalp; Sperschneider, Jana; Malar C, Mathu; Chen, Eric C. H.; Iwasaki, Wataru; Cornell, Calvin; Corradi, Nicolas
Summary: Chromosome folding links genome structure with gene function by generating distinct nuclear compartments and topologically associating domains. In mammals, these undergo preferential interactions and regulate gene expression. However, their role in fungal genome biology is unclear. Here, we combine Nanopore (ONT) sequencing with chromatin conformation capture sequencing (Hi‐C) to reveal chromosome and epigenetic diversity in a group of obligate plant symbionts: the arbuscular mycorrhizal fungi (AMF). We find that five phylogenetically distinct strains of the model AMF Rhizophagus irregularis carry 33 chromosomes with substantial within‐species variability in size, as well as in gene and repeat content. Strain‐specific Hi‐C contact maps reveal a 'checkerboard' pattern that underline two dominant euchromatin (A) and heterochromatin (B) compartments. Each compartment differs in the level of gene transcription, regulation of candidate effectors and methylation frequencies. The A‐compartment is more gene‐dense and contains most core genes, while the B‐compartment is more repeat‐rich and has higher rates of chromosomal rearrangement. While the B‐compartment is transcriptionally repressed, it has significantly more secreted proteins and in planta upregulated candidate effectors, suggesting a possible host‐induced change in chromosome conformation. Overall, this study provides a fine‐scale view into the genome biology and evolution of model plant symbionts, and opens avenues to study the epigenetic mechanisms that modify chromosome folding during host–microbe interactions.